(untitled) (World Bulletin of Social Sciences, 2022)
The article describes the theoretical and practical experience of selecting young volleyball players and technologies for improving their technicalskills. Training of young athletes takes place in stages. During training, young volleyball players master the elements of volleyball technique and tactics, develop their physical qualities. At the same time, young athletes are trained spiritually, morally and spiritually. The preparatory period is held before the start of the competition